Bryan Montgomery Collection - Hyman, James; Montgomery, Bryan; Newlan, Ken; Tóth, Ferenc (Budapest : Museum of Fine Art, 1999)
Ainsworth, Mark ; Appel, Karel ; Berg, Adrian ; Beuys, Joseph ; Boshier, Derek ; Bottle, Ian ; Briggs, Lamar ; Cannon, John ; Castillo, Jorge ; Cina, Colin ; Craig-Martin, Michael ; Donagh, Rita ; Dubsky, Mario ; Farrell, Michael ; Faulkner, Armando ; Ginsborg, Michael ; Green, Alan ; Groom, Jon ; Hambling, Maggi ; Hamlyn, Paul ; Hayter, Stanley William ; Hoyland, John ; Huxley, Paul ; Jacklin, Bill ; Jarman, Derek ; Kelly, Ellsworth ; Kemp, Lindsay ; Lancaster, Mark ; Latter, Jim ; Leverett, David ; Lewis, Peter Nicholas ; Lintine, David ; McKeever, Ian ; Martin, Kenneth ; Martin, Mary ; Masterson, Stephen ; Maybury, John ; Milow, Keith ; Negret, Edgar ; Newlan, Ken ; Noland, Kenneth ; Plumb, John ; Poll, Bas Van der ; Prouveur, Jean-Marc ; Rothenstein, Michael ; Ruscha, Edward ; Schofield, David ; Stella, Frank ; Stephenson, Ian ; Tappert, Georg ; Tilson, Joe ; Tyzack, Michael ; Vasarely, Victor ; Wakefield, Sebastian ; Walker, John ; Ward, David ; Yule, Ainslie ; Zapkus, Kestutis
biog.
Bryan Montgomery Collection, Museum of Fine Art Budapest, 1999
Engels
Hongaars
boek